ANALISIS FAKTOR-FAKTOR PENYEBAB FRAUD PADA BADAN USAHA MILIK DAERAH (STUDI DI PERUSAHAAN DAERAH BANK PERKREDITAN RAKYAT BANK DAERAH X) - Muhamad Erfin Fatoni; Abdul Halim (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2016)
The purpose of this research is to analyze the factors that cause the occurrence of fraud in PD BPR Bank Dearah X which is one of the regional owned enterprises of Local Government X and identify the steps ways of fraud prevention which is effective in PD BPR Bank Daerah X. This research uses a qualitative approach with a case study. This study uses the primary data and secondary data. This research uses many data collection techniques by conducting an interview, an observation and a documentation. The results show that the factors that cause the occurrence of fraud in PD BPR Bank Daerah X can be classified into four, namely: (1) the pressure that comes from the external and internal influence, (2) an opportunity or a chance due to the weakness of internal control systems owned by BPR , sanctions are not strict enough for the wrongdoers of fraud, and misuse of authority committed by directors, (3) rationalization, and (4) collusion. The ways of fraud prevention which are done by the management of PD BPR Bank Daerah X and based on the results of interviews conducted by the researchers, can be identified as follows: (1) An improvement of the internal control system in PD BPR Bank Daerah X, (2) An implementation of policy of know your employee (KYE) as an effort of fraud prevention by controlling the aspects of human resources (HR); (3) A creation of a special line of fraud reporting policy;and (4) An establishment of policies and sanction procedures.